Exploring the Relationship Between Self-Stigma and Mental Health Among People with Substance Use Disorder - Wagma Iqbal; Sara khan; Jaweria; Hasnain Hyder; Hamad Saeed (Research Journal of Psychology, 2025)
This study aims to find out the relationship between self stigma and mental health outcomes (depression and anxiety) among substance use disorder (SUD) people in Peshawar, Pakistan. The purpose was to examine how self stigma influences psychological well being and to investigate a mediating role of social support. A total of 150 participants receiving treatment at public and private rehabilitation centers were surveyed using validated self-report instruments: Self-Stigma of Seeking Help Scale (SSSHS), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7) and Multidimensional Scale of Perceived Social Support (MSPSS). The analyses indicate that there is significant positive correlation between depression and anxiety with self stigmatization. Additionally, social support was causally related to the effects self stigma has on mental health outcomes, in a way that partially mediates this relationship, lending partial support to the buffering hypothesis. The results highlight the importance of self stigma and social support in contributing to mental health outcomes of SUD and reduce psychological distress of stigma. The paper makes the point that stigmatization reduction interventions and strong social systems of support need to be built in the rehabilitation programs especially in the culture where addiction is highly stigmatized. Future research should also examine these relationships longitudinally and examine cultural variation in self stigma and recovery processes.